1995
DOI: 10.1038/bjc.1995.76
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin expression in renal cell cancer and its significance in metastasis and survival

Abstract: Sumary Decreased expression of E-cadherin (E-CD). a homotypic intercellular adhesion molecule, is considered to elicit detachment of tumour cells from primary lesions, which is the first stage of metastasis. Since renal cell cancer (RCC) shows a relatively high frequency of metastasis, we focused our interest on E-CD expression in RCC and its clinicopathological implications. We examined E-CD expression in normnal kidney and RCC by immunohistochemical staining. In normal kidney, E-CD expression was localised i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
75
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 9 publications
7
75
1
1
Order By: Relevance
“…Therefore, lack of Ksp-cadherin protein expression in RCC tumour tissues seems to be in accordance with the origin of the tumours. However, expression of E-cadherin on RCC tumour cells, which due to the origin must be regarded as an aberrant expression pattern, can be correlated with tumour stages but not with survival rates (Katagiri et al, 1995;Shimazui et al, 1997). It will be a challenge for the near future to determine in a larger cohort of patients whether the expression of Ksp-cadherin mRNA can also be correlated with different tumour stages or survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lack of Ksp-cadherin protein expression in RCC tumour tissues seems to be in accordance with the origin of the tumours. However, expression of E-cadherin on RCC tumour cells, which due to the origin must be regarded as an aberrant expression pattern, can be correlated with tumour stages but not with survival rates (Katagiri et al, 1995;Shimazui et al, 1997). It will be a challenge for the near future to determine in a larger cohort of patients whether the expression of Ksp-cadherin mRNA can also be correlated with different tumour stages or survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reduced levels of E-cadherin expression would facilitate a decrease in cellular and tissue differentiation and result in a higher pathologic grade. Katagiri et al 26 found that the frequency of E-cadherin expression in RCC is lower than in other cancers. This may be due to the more localized distribution of E-cadherin expression in the normal kidney compared with other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of E-cadherin have been reported previously to be associated with an increased risk for the development of metastasis in human tumors, [55][56][57] including RCC. 26 E-cadherin is a calcium-dependent cell adhesion molecule that is important in cell-cell interactions in the epithelium and thus plays a major role in organizing and maintaining the structure and integrity of epithelial sheets. Cell detachment is one of the necessary steps in the process of metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of these genes are hypothesized to be an important step in the progression from tumor formation to invasion and metastasis. 10 These genes and some other cadherin family members are located on the long arm of chromosome 16 (16q), 11 a chromosomal location that is frequently deleted in breast and other types of carcinomas. [12][13][14][15][16] On the basis of Knudson's 17 "two-hit" hypothesis, both alleles of tumor suppressor genes have to be inactivated for loss of expression.…”
mentioning
confidence: 99%